Navigating the challenges: ultrasound innovations in brain glioma surgery - Sadrinasab, Shayan; Aminiyan, Armin; Saket, Sadaf; Khosravi, Fatemeh; Pourmohammadi, Nadia; Saadat Fakhr, Masoud (Frontiers in Neurology, 2025)
Achieving maximal safe resection during glioma surgery while preserving neurological function remains a significant challenge. Intraoperative ultrasound (IOUS) offers real-time imaging that dynamically adapts to brain shift and surgical progression. This review highlights recent advances in IOUS, including established modalities such as contrast-enhanced and 3D ultrasound, and emerging innovations such as functional ultrasound (FUS), 4D volumetric imaging, artificial intelligence (AI)-assisted interpretation, and ultrasound-sensitive nanobubbles. These technologies aim to improve the identification of residual tumor, delineate infiltrative margins, and enable functional preservation. Integration with neuronavigation systems enhances accuracy, while new theranostic strategies suggest a future role for ultrasound in intraoperative therapy. Collectively, these developments position IOUS as a central component in the evolution of precision glioma surgery.